2014
DOI: 10.1242/jcs.138230
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Cx30 that are linked to skin disease and non-syndromic hearing loss exhibit several distinct cellular pathologies

Abstract: Connexin 30 (Cx30), a member of the large gap junction protein family, plays a role in the homeostasis of the epidermis and inner ear through gap junctional intercellular communication (GJIC). Here, we investigated the underlying mechanisms of four autosomal dominant Cx30 gene mutations linked to hearing loss and/or various skin diseases. First, the T5M mutant linked to non-syndromic hearing loss formed functional gap junction channels and hemichannels, similar to wild type Cx30. The loss-of-function V37E muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 105 publications
4
58
1
Order By: Relevance
“…Whether these clinical presentations are associated with the disruption of the normal Cx30 life cycle or function, or whether they are due to any gainof-or loss-of-function mutant effect on other co-expressed connexins, remains poorly understood. Surprisingly, we have previously shown that some Cx30 mutants acquire new properties and can affect the localization of Cx43 (Berger et al, 2014), even though here we show that wild-type Cx30 remains in distinct subplaque domains from Cx43. One explanation for connexin segregation could be due to the wealth of Cx43 binding partners while the interactome for Cx30 is limited due to the small C-terminal domain (Laird, 2010).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Whether these clinical presentations are associated with the disruption of the normal Cx30 life cycle or function, or whether they are due to any gainof-or loss-of-function mutant effect on other co-expressed connexins, remains poorly understood. Surprisingly, we have previously shown that some Cx30 mutants acquire new properties and can affect the localization of Cx43 (Berger et al, 2014), even though here we show that wild-type Cx30 remains in distinct subplaque domains from Cx43. One explanation for connexin segregation could be due to the wealth of Cx43 binding partners while the interactome for Cx30 is limited due to the small C-terminal domain (Laird, 2010).…”
Section: Discussioncontrasting
confidence: 79%
“…We have previously shown that the presence of GFP does not affect the ability for Cx30 to traffic to the cell surface and form functional gap junction channels and hemichannels (Berger et al, 2014). While a few Cx30 plaques were dynamic, splitting up and Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several deafnessassociated Cx26, Cx29, Cx30, and Cx31 mutants have been shown to be trapped in the ER and are unable to transport to the plasma membrane in transfected cells [98][99][100][101][102]. Moreover, Bip/GRP78 is upregulated in Cx31R180X-or Cx31E183K-overexpressed cells, suggesting that ER stress is elevated by these Cx31 mutations [101].…”
Section: Connexins and Er Stressmentioning
confidence: 99%